STUDI INSTRUMEN KEBIJAKAN GERAKAN TERPADU KESEHATAN, EKONOMI, PENDINDIKAN, LINGKUNGAN, INFRASTUKTUR (GERDU KEMPLING) KELURAHAN BULUSAN KOTA SEMARANG - Pratiwinegara, Agatha Idriani; Suwitri, Sri; Santoso, R. Slamet (Journal of Public Policy and Management Review, 2015)
An integrated movement of health, economic, education, infrastucture, enviroment (GERDU KEMPLING) program in Semarang is a policy about accelerating proverty reduction and the real action of â€œSapta Programâ€ from Semarang Goverment. The policy has a goal for reaching the decreacing of provertyâ€™s level in 2011 â€“ 2015 at Semarang. In the first idea, it has been planned that the policy would invite all sectors in Semarang, including private sectors and the citizen. Then a policy can be applied well, if it uses a correct policy instrument in its implementation. And in this research, it will discuss about which one of policy instrument that has been used in Gerdu Kempling program. The result shows in implementing this policy, the actors use mixed instrument, and more head for subsidies instrument. Itâ€™s proved by there are mixturing among regulation from compulsary instrument and family and community and market from voluntary instrument. After that, the subsidies instrument can be proved by types of help that have been given to poor citizen, which are coaching and tools. In other hand, in implementing this policy with mixed instrument has some problems in it. Over all, the problems are about support instruments have not maximal in their action.